CRISPR activation: identifying and using novel genes for plant disease resistance breeding - McLaughlin, John E.; Kue Foka, Idrice Carther; Lawton, Michael A.; Di, Rong (Frontiers in Genome Editing, 2025)
CRISPR-based technologies have revolutionized plant science by enabling precise modulation of gene function, including CRISPR activation (CRISPRa), a recently emerging strategy which shows particular promise for enhancing disease resistance through targeted gene upregulation. Unlike conventional CRISPR editing, which introduces double-stranded DNA breaks and permanent genomic changes, CRISPRa employs a deactivated Cas9 (dCas9) fused to transcriptional activators. This system allows quantitative and reversible gene activation without altering the DNA sequence, offering a gain-of-function (GOF) like enhanced blight resistance in staple crops. Despite its potential, the limited adoption of CRISPRa in plant biology to date underscores the need for future studies to fully harness its capabilities for crop improvement. This review addresses the groundbreaking and relatively underexplored potential of CRISPR activation (CRISPRa) systems for GOF studies in plant biology, and advocates for the adoption of CRISPRa to discover and harness genetic variation for enhancing disease resistance. We present recent advancements in CRISPRa technology, emphasizing its successful application in boosting plant immunity. Moreover, we discuss the synergistic potential of integrating CRISPRa with functional genomics tools such as genome-wide association studies (GWAS) and multi-omics approaches to identify and characterize key resistance genes. Additionally, we highlight ongoing progress in developing plant-specific programmable transcriptional activators (PTAs) to optimize CRISPRa efficiency. Challenges associated with achieving transgene-free overexpression and the deployment of alternative CRISPR systems are also explored. Together, these advances position CRISPRa as a transformative tool for future crop breeding strategies aimed at achieving durable, broad-spectrum disease resistance and sustainability in agriculture.